Overview of Effects of Motor Learning Strategies in Neurologic and Geriatric Populations: A Systematic Mapping Review - Li-Juan Jie, PhD; Melanie Kleynen, PhD; Guus Rothuizen, MSc; Elmar Kal, PhD; Andreas Rothgangel, PhD; Susy Braun, PhD (Archives of Rehabilitation Research and Clinical Translation)
Objective: To provide a broad overview of the current state of research regarding the effects of 7 commonly used motor learning strategies to improve functional tasks within older neurologic and geriatric populations. Data Sources: PubMed, CINAHL, and Embase were searched. Study Selection: A systematic mapping review of randomized controlled trials was conducted regarding the effectiveness of 7 motor learning strategies—errorless learning, analogy learning, observational learning, trial-and-error learning, dual-task learning, discovery learning, and movement imagery—within the geriatric and neurologic population. Data Extraction: Two thousand and ninety-nine articles were identified. After screening, 87 articles were included for further analysis. Two reviewers extracted descriptive data regarding the population, type of motor learning strategy/intervention, frequency and total duration intervention, task trained, movement performance measures, assessment time points, and between-group effects of the included studies. The risk of bias 2 tool was used to assess bias; additionally, papers underwent screening for sample size justification. Data Synthesis: Identified articles regarding the effects of the targeted motor learning strategies started around the year 2000 and mainly emerged in 2010. Eight populations were included, for example, Parkinson's and stroke. Included studies were not equally balanced: analogy learning (n=2), errorless learning and trial-and-error learning (n=5), mental practice (n=19), observational learning (n=11), discovery learning (n=0), and dual-tasking (n=50). Overall studies showed a moderate-to-high risk of bias. Four studies were deemed sufficiently reliable to interpret effects. Positive trends regarding the effects were observed for dual-tasking, observational learning, and movement imagery. Conclusions: Findings show a skewed distribution of studies across motor learning interventions, especially toward dual-tasking. Methodological shortcomings make it difficult to draw firm conclusions regarding the effectiveness of motor learning strategies to improve functional studies. Future researchers are strongly advised to follow guidelines that aid in maintaining methodological quality. Moreover, alternative designs fitting the complex practice situation should be considered.